PERBANDINGAN MASSA OPTIMUM CAMPURAN PEWARNA ALAMI PADA KAYU JENIS AKASIA (Acacia leucopholea) - N. W. Bogoriani; A. A. Bawa Putra (Program Studi Kimia, FMIPA, Universitas Udayana (Program of Study in Chemistry, Faculty of Mathematics and Natural Sciences, Udayana University), Bali, Indonesia, 2009)
Wood is one of several materials that is very useful for man. Now adays wood with low quality tends to beused more. The high demand causes good quality wood getting harder to find. To overcome this problem, low qualitywood like acacia was dyed using a mixture of natural dye. The dye was prepared from urcaria gambir-piper betleLinn leaves, areca catechw seed, and 0.5 % w/v of CaCO3 in water. The physical and chemical properties of thedyed wood was tested using aluminium sulphate solution and detergent solution.The optimum mass for the dye was 5.3 uncaria : 3.0 piper; 3.0 areca. After 30 minutes soaking in themixture, reddish brown coolour was produced, with maximum adsorption of 0.23 g in wood surface that showeddurability of the dye highest from dye appearance and mixture mass that be lost.